Runoff from upstream changes the structure and energy flow of food web in estuary - Yi, Yujun; Zhao, Fanxuan; Liu, Qi; Song, Jie (Frontiers in Marine Science, 2023)
Sediment and nutrients flow into estuary with runoff, and then influence the estuary ecosystem. Much work has been done for investigating the response of water quality and species group (eg. phytoplankton or zooplankton) to the runoff from upstream, while few research has been taken to evaluate the response of the whole ecosystem. This work selects the typical weak tide estuary, Yellow River Estuary (YRE), to evaluate the influence of runoff on food web in estuary. Food webs of different seasons and regions were established based on stable isotope analysis and Bayesian mixing model. The influences of upstream runoff and sediment transport on the estuarine food webs were analyzed. The results show that food web in estuary has highly spatial-temporal variability. The area with high-turbidity freshwater inflow nurtured more terrestrial- organic- matter (TOM) relying species. The contribution of TOM to food web was higher in flood season than that in non-flood season. That would be because that the input and diffusion of sediment and nutrients carried by runoff led to the changes in the dietary structure of estuarine organisms and the decrease in trophic levels of major predators. At the same time, flow pulse with high sediment can also aggravate the spatial differences of the structure of food webs. The southern shore with higher sediment concentration provided a harsher environment to organisms, leading to low nutrient diversity and hence a less complex food web. However, the increased input of TOM enhanced the links density and connectance of food web, making it a more robust system. These results have guiding significance for research on energy flow mechanisms in estuarine ecosystems affected by both terrestrial runoff and ocean tides, as well as artificial upstream hydrological regulation.